Predictors of response to therapy with omalizumab in patients with severe allergic asthma – a real life study. Issue 6 (18th August 2017) - Kallieri, Maria; Papaioannou, Andriana I.; Papathanasiou, Evgenia; Ntontsi, Polyxeni; Papiris, Spyridon; Loukides, Stelios
ABSTRACT: Objectives : Omalizumab is a recombinant humanized IgG1 monoclonal anti-IgE antibody, used for the treatment of severe refractory allergic asthma. However, not all patients with IgE levels within the limits of administration, respond to treatment. The aim of the present study, was to determine clinical and inflammatory characteristics that could predict response to omalizumab. Methods : We studied retrospectively patients treated with omalizumab as per GINA guidelines in one asthma tertiary referral center. Demographic and functional characteristics, level of asthma control, fractional exhaled nitric oxide, blood and eosinophils and IgE level, induced sputum cell count, eosinophil cationic protein and Interleukin-13 in sputum supernatant were recorded. All measurements were performed before starting treatment with omalizumab. Response to treatment was evaluated according to the physician's global evaluation of treatment effectiveness. Patients were characterized as early responders when improvement was achieved within 16 weeks and as late responders when improvement was achieved between 16 and 32 weeks. Patients who did not show any improvement after 32 weeks of therapy were considered as non-responders. Results : Forty-one patients treated with omalizumab were included in the study. 28 (68.3%) patients were characterized as responders while 13 patients (31.7%) were considered as non-responders. Among responders, 25 (89%) were early responders and 3 (n = 11%) were late responders. Responders were characterized by lower baseline FEV1 and FEV1 /FVC and higher IL-13 levels in induced sputum supernatant compared to non-responders. Late responders had higher serum IgE levels, shorter disease duration and higher number of blood eosinophils. Finally, using ROC curve analysis, the best predictors of response to omalizumab were FEV1 (AUC = 0.718) and IL-13 in sputum supernatant (AUC = 0.709). Conclusion : Lower baseline FEV1 and higher IL-13 levels in induced sputum supernatant were predictors of response to omalizumab. Patients with higher baseline serum IgE levels, shorter disease duration and higher blood eosinophils may experience a late response and might benefit from a more prolonged treatment before being characterized as non-responders.